The Latin American and Caribbean university, Challenges in the XXI Century - Soto Arango, Diana Elvira; Forero Romero, Aracely (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2016)
This paper examines the course of events that created the current framework of the universities in Latin American and Caribbean in the late XXI century. This study arose from research conducted in the group HISULA, which has established a network of Latin American researchers who have reflected upon the university during 24 years. The aim of this study is to recognize the contribution of these research works from a diachronic vision of the university reality. In this context, we relied on the social history of education method, the paradigm developed by SHELA, and the prospective method. The first stage of this research focused on defining the present positioning of Latin American universities. With this purpose, we carried out a review of the major influences that have led to the current state of higher education institutions in the Latin American and Caribbean continent, from the different market contexts that point to globalization versus knowledge society, mediated by innovation. Second, it is located in the predominant curricular trends that influence learning and innovation processes and the role of technology evolution in the paths undertaken by Institutions of Higher Education in Latin America and the Caribbean.Third, we analyze the opinions and ‘imaginaries’ of the directors of the Universidad Pedagogica y Tecnologica de Colombia, through five factors analysis, as a sample of regional university in Colombia. Research strategies focused on document review, such as legislation, reports, and interviews with UPTC directors who envisioned the institution from policies on quality and research, but did not present hypotheses about the future of the University;. Their concern focused on meeting the requirements arising from state regulation of the education sector. It is concluded that the market economy goes against the essence of the university as a public service for society, and ICT in teaching and learning processes have failed to spread humanistic education. The great challenge is to make the transition from institutional identity towards the identity of a Latin American and Caribbean university.